Analisis Kualitas Kerja Pegawai Kantor Kelurahan Teddaopu Kecamatan Tempe Kabupaten Wajo - Muh. Hasbi Abbas; Yusran Yusran; Asmanurhidayani (Perspektif Administrasi Publik dan hukum, 2025)
The background of this research, in accordance with the hail observations that have been carried out, is that there are still often problems about the existence of unprofessional employees or lack of discipline in work such as the existence of employees who are not on time. The purpose of this study is to find out and analyze the quality of work of employees of the Teddaopu Village Office, Tempe District, Wajo Regency, The type of research conducted is a type of descriptive qualitative research using data collection techniques through observation, interviews and documentation which aims to examine the analysis of the quality of work of employees of the Teddaopu Village Office. The data analysis technique goes through various stages, namely data reduction, data presentation and conclusion drawn, while the data validity technique uses credibility, transferability, dependability, and confirmability tests. The results of this study show that the quality of work of the employees of the Teddaopu Village Office has been running well, including the quality in terms of community services has been running properly, transparent, the employees always listen to the complaints of the community, always make plans in advance before doing work, but in terms of human resources it can be seen from the lack of communication of several employees at the Teddaopu Village Office, Tempe District Wajo Regency, Discipline in working hours and lack of facilities and infrastructure regarding parking lots. The conclusion is that the quality of work of the Teddaopu Village office employees has gone well.